Difference between estimated glomerular filtration rate based on cystatin C versus creatinine and cardiovascular–kidney–metabolic health - Wu, Xiaoyan; Hu, Wuming; Xu, Jian; Shen, Jiayi; Lin, Li; Zhu, Jingshuai; Wei, Tiemin; Lv, Lingchun (Frontiers in Medicine, 2025)
BackgroundThe difference between the estimated glomerular filtration rate (eGFR) calculated from cystatin C and creatinine (eGFRdiff) serves as a biomarker of kidney function impairment. However, the role of eGFRdiff in cardiovascular–kidney–metabolic (CKM) health and its impact on mortality in CKM syndrome patients has not yet been studied.MethodsThis study included 3,622 participants from the National Health and Nutrition Examination Survey (NHANES) conducted between 1999 and 2004. Weighted ordinal logistic regression was used to explore the link between eGFRdiff and CKM health, while weighted Cox regression was used to examine the relationship between eGFRdiff and mortality in CKM syndrome patients. Restricted cubic splines (RCSs) were used to analyze the dose–response relationship.ResultsThe common odds ratio (cOR) per 10 mL/min/1.73m2 increase in eGFRdiff was 0.86 [95% confidence interval (CI), 0.81 to 0.91]. Compared to the midrange eGFRdiff, the cOR values for the negative and positive eGFRdiff were 1.88 [95% CI, 1.23 to 2.88] and 0.69 [95% CI, 0.58 to 0.83], respectively. During a median follow-up of 201 months, 853 participants died from all causes, while 265 died due to cardiovascular causes. The hazard ratios (HRs) per 10 mL/min/1.73m2 increase in eGFRdiff were 0.88 [95% CI, 0.83 to 0.93] for all-cause mortality and 0.90 [95% CI, 0.81 to 1.00] for cardiovascular mortality cases. Compared to the participants with a midrange eGFRdiff, those with negative eGFRdiff had a 48% higher risk of all-cause mortality, while those with positive eGFRdiff had a 30% lower risk. No significant non-linear associations were found in these regression analyses.ConclusionOur study found that eGFRdiff is associated with CKM health and stratified mortality risk in CKM syndrome patients.